Evaluation of pathological problems associated with carbonation and sulfates in a concrete tower with more than 50 years in service - Maldonado Bandala, Erick Edgar; Nieves Mendoza, Demetrio; Vela Jimenez, Juan Luis; Castro Borges, Pedro (Revista ALCONPAT, 2018)
In preparation for rehabilitation of a 50+ year-old reinforced concrete tower in the southern portion of the state of Veracruz, Mexico, inspections and assays were done to quantify corrosion in the structure. Visual damage survey was done using an aerial drone, and physical, chemical, mechanical and electrochemical assays run to characterize concrete condition and corrosion damage. Carbonation is the predominant corrosion mechanism in the structure. Sulfate emission in the surrounding industrial installations is reflected in low compression resistance, cracks and spalling. Considering the concrete condition and corrosion results, a five-step repair and rehabilitation process is proposed to extend structure service life.